Towards photophoresis with the generalized Lorenz-Mie theory. (September 2022) - Ambrosio, Leonardo André; Wang, Jiajie; Gouesbet, Gérard
Highlights: We introduce optical forces from thermal origins with the aid of the generalized Lorenz-Mie theory (GLMT) It is, to the best of the authors' knowledge, the first formal analysis to describe photophoresis with the GLMT stricto sensu Analytical formulas are presented for the cartesian components of the asymmetry vector, which is proportional to photophoretic forces Results are valid both in the slip-flow and in the continuous regime and for any arbitrary shaped beam Abstract: Based on the adjoint boundary value problem proposed decades ago by Zulehner and Rohatschek [1], analytic and closed-form expressions for the photophoretic forces exerted by arbitrary-shaped beams on homogeneous and low-loss spherical particles is derived in both the free molecular and slip flow regimes. To do so, the asymmetry vector for arbitrary refractive index particles is explicitly calculated by expanding the internal electromagnetic fields with the aid of the generalized Lorenz-Mie theory (GLMT). The approach here proposed is, to the best of the authors' knowledge, the first systematic attempt to incorporate the GLMT stricto sensu into the field of photophoresis and might as well be extended, e.g. to spheroids and find important applications, among others, in optical trapping and manipulation of microparticles, in geoengineering, particle levitation, optical trap displays and so on.